Fenugreek Seeds Extracts as Growth Regulatory and Feeding Inhibitor for the African Melon Lady Bird Beetle Henosepilachna elaterii (Rossi) - Mahmoud , Asma Khalid; Abdelbagi, Azhari Omer (University of Khartoum Journal of Agricultural Sciences, 2023)
This study aimed at investigating the effect of the extracts of fenugreek seeds on feeding and development of the African melon ladybird beetle, Henosepilachna elaterii. (Rossi). Seeds of fenugreek (Trigonella foenum-graceum) were extracted by distilled water and organic solvents (chloroform, acetone and ethanol), and the extracts were tested against the African melon ladybird beetle under laboratory conditions. Both aqueous and organic extracts showed significant growth regulatory activities, mainly prolonging the larval duration. The effect was clear in late instars. The organic extracts showed strong feeding inhibitory activity against the fourth larval instar, where the amounts of food consumed inversely related to dose. The effects induced by acetone and ethanol extracts were greater than chloroform extract. Phytochemical groups present in various fractions were identified. Various aspects of efficacy against the test insect are discussed